Analyses of Sustainable Water Management Practices in Nigerian Building Projects - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S.; B., Dan-asabe; A.A., Alabi (Journal of Infrastructural in Civil Engineering, 2025)
This study examines sustainable water management practices in Nigerian building projects, focusing on current practices, barriers, enablers, and comparisons with global standards. Data were collected from 272 stakeholders, including architects, engineers, contractors, policymakers, and building occupants. Findings reveal partial adoption of water conservation practices, with significant barriers such as financial constraints, lack of technical expertise, and inadequate regulatory frameworks. Key enablers identified include increasing stakeholder awareness, government incentives, and international cooperation. Cluster and factor analyses highlight patterns and dimensions of water management practices. Case studies from Lagos and Abuja demonstrate the feasibility and benefits of comprehensive water management plans. The study concludes that addressing financial and technical barriers and leveraging enablers is essential for advancing sustainable water management in Nigeria, providing valuable insights for policymakers, industry stakeholders, and researchers.